Laccases stabilization with phosphatidylcholine liposomes - Martí, M. (2012)
In recent years, there has been an upsurge of interest in enzyme treatment of textile fibres. Enzymes are globular proteins whose catalytic function is due to their three dimensional structure. For this reason, stability strategies make use of compounds that avoid dismantling or distorting protein 3D structures. This study is concerned with the use of microencapsulation techniques to optimize enzyme stabilization. Laccases were embedded in phophatidylcholine liposomes and their encapsulation capacity was assessed. Their enzymatic activity and stability were analyzed, comparing free-enzymes, enzymes in liposomes, and the lipid fraction separated from the aqueous fraction. An increase in their encapsulation efficiency was found at higher lipid/laccase ratios. Relative activity of enzyme-containing vesicles has also been shown to be retained much more than that of free native enzymes. The loss of activity of laccases entrapped in the vesicles in the total stability process is lower than 10% compared with 40% to 60% of loss of free-laccases after heating the samples for 3 days. Laccase stabilization could be of interest to future textile or cosmetic applications because of their potential for environmentally friendly oxidation technologies.